MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN PADA ANAK MELALUI PENGGUNAAN MEDIA FLIPBOOK - Winda Oktaviana (Fakultas Pendidikan, Universitas Sultan Muhammad Syafiuddin Sambas, 2022)
Abstrak Beginning reading ability is an important ability to develop in children. This study aims to develop early reading skills in children using Flipbook media at TK IT Darul Hikmah Mumtaza City of Sungai Penuh. This study used a collaborative classroom action research approach. The sampling technique is cluster sampling. Data collection techniques are observation, interviews and documentation. Teknik analisis data yang digunakan yaitu analisis kuantitatif dengan persentase dan analisis kualitatif. The results showed that there was an increase in initial reading ability, namely in the pre-cycle conditions of 48.8% increased in cycle I to 60.83%, in cycle II it increased by 75% and in cycle III to 88.33% with very good development criteria. Thus it can be concluded that Flipbook media can develop children's early reading skills in the TK IT Darul Hikmah Mumtaza, Sungai Penuh City. In implication, the use of Flipbook media shows a more optimal development of early reading skills in children.